2018
DOI: 10.1021/jacs.7b13796
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Heavy Alkaline Earth Metal–Hydrogen Bond: Synthesis, Structure, and Reactivity of a Cationic Strontium Hydride Cluster

Abstract: The molecular strontium hydride [(MeTACD)Sr(μ-H)][SiPh] (2) was isolated as the dark red benzene solvate 2·CH in 69% yield from the reaction of [Sr(SiPh)(thf)] (1') with (MeTACD)H (1,4,7-trimethyl-1,4,7,10-tetraazacyclododecane). This reaction can be considered as a redox process, with the Brønsted acidic amine proton in (MeTACD)H transformed into the hydride by the anion [SiPh]. Trace amounts of water resulted in the formation of [(MeTACD)Sr(μ-H)(μ-OH)][SiPh] (2*), which cocrystallized with 2. Single-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 102 publications
0
39
0
3
Order By: Relevance
“…Crystal structure of 4‐Sr is similar to 2‐Ca except for the coordinated donor solvent. The Sr−H distances ( 2.26(5) and 2.28(5) Å) are significantly shorter than those in complexes [L Ad Sr( μ ‐H)] 2 (2.38(3) and 2.43(3) Å), Sr 6 H 9 [N(SiMe 3 ) 2 ] 3 (PMDTA) 3 (2.38(4)–2.78(8) Å) and [(Me 3 TACD) 3 Sr 3 H 2 ][SiPh 3 ] (2.43(4)–2.60(4) Å) …”
Section: Methodsmentioning
confidence: 91%
“…Crystal structure of 4‐Sr is similar to 2‐Ca except for the coordinated donor solvent. The Sr−H distances ( 2.26(5) and 2.28(5) Å) are significantly shorter than those in complexes [L Ad Sr( μ ‐H)] 2 (2.38(3) and 2.43(3) Å), Sr 6 H 9 [N(SiMe 3 ) 2 ] 3 (PMDTA) 3 (2.38(4)–2.78(8) Å) and [(Me 3 TACD) 3 Sr 3 H 2 ][SiPh 3 ] (2.43(4)–2.60(4) Å) …”
Section: Methodsmentioning
confidence: 91%
“…Ther esonance for the hydride ligands appears as as inglet at d = 3.99 ppm in [D 8 ]THF.T he strontium homologue of 4d [(Me 3 TACD) 3 Sr 3 -(m 3 -H) 2 ][SiPh 3 ]·C 6 H 6 was also reported. [37] Bis(triphenylsilyl)calcium [Ca(SiPh 3 ) 2 (thf) 4 ]u ndergoes quantitative hydrogenolysis (1 bar,6 08 8C) in [D 6 ]benzene to give two equivalents of Ph 3 SiH and some form of colloidal calcium hydride [CaH 2 (L) n ] m (L = solvent) of unknown composition, which shows av ery broad proton resonance at d = 3.9-5.4 ppm for the hydride ligands. [38]…”
Section: [Me 3 Tacd] à (L 3 X) 241 Synthesis and Characterizationmentioning
confidence: 99%
“…The coordination numbers for calcium vary from 4to9,while the hydrides exhibit m 2 -tom 6 -bridging bonding modes.Aterminal calcium hydride,w hich is expected to be extremely reactive, remains elusive,b ut may play ar ole in hydrogenation and hydrofunctionalization catalysis.S everal recent discoveries such as n-alkene and benzene alkylation [30] as well as CO [28] and H 2 [40,41] activation will surely boost this research area further. Molecular hydrides of the heavier strontium [37,39,46] and barium [15c,47] have also appeared recently.H omogeneous catalysis by soluble alkaline earth metal compounds is already arapidly growing area, [48] with the hydrido complexes playing ac entral role.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…[11] In 2008, Harder and coworkers [12] reported the use of NacNac dippcalcium and strontium complexes (dipp = 2,6-diisopropylphenyl;N acNac dipp = CH{(CMe)(2,6-iPr 2 C 6 H 3 N)} 2 )t oe ffect the hydrogenation of olefins,a nd showed that related alkalimetal systems require high H 2 pressures (100 bar). Subsequently,t hese Group 2s ystems were expanded to include Okudasw ork on trimetallic calcium [13] and strontium [14] hydride cations,[ (Me 3 TACD) 3 M 3 (m 3 -H) 2 ] + (Me 3 TACD = 1,4,7-trimethyl-1,4,7,10-tetraazacyclododecane;M= Ca, Sr), which also acts as ahydrogenation catalyst for Ph 2 CCH 2 .V ery recently,H arder et al [15] reported the use of the Group 2 metal amides M[N(SiMe 3 ) 2 ] 2 ,M= Mg, Ca, Sr, Ba) as hydrogenation catalysts for imine reduction. Herein, we examine Group 1m etal species,e xploiting some of our insights garnered from FLP chemistry.W ed emonstrate that the species MX (M = Li, Na, K; X= P(tBu) 2 ,N(SiMe 3 ) 2 ,PhCH 2 , H) activate dihydrogen reversibly,r evealing the ability to cause hydrogen isotope exchange in the toluene methyl group via amechanism that is analogous to the FLP activation of H 2 .As olution of LiP(tBu) 2 in C 6 D 6 was exposed to HD at 50 8 8Cf or 20 h( Scheme 1).…”
mentioning
confidence: 99%